Effect of an Educational Presentation about Extremely Preterm Infants on Knowledge and Attitudes of Health Care Providers - Doucette, Stefani; Lemyre, Brigitte; Daboval, Thierry; Dunn, Sandra; Akiki, Salwa; Barrowman, Nick; Moore, Gregory P. (American Journal of Perinatology, 2017)
Objective To determine healthcare providers' knowledge (HCP) about survival rates of extremely preterm infants (EPI) and attitudes toward resuscitation before and after an educational presentation and, to examine the relationship between knowledge and attitudes toward resuscitation.Study Design Participants completed a survey before and after attending a presentation detailing evidence-based estimates of survival rates and surrounding ethical issues. Respondents included neonatologists, obstetricians, pediatricians, maternal-fetal medicine specialists, trainees in pediatrics, obstetrics, neonatal-perinatal medicine and neonatal and obstetrical nurses.Results In total, 166 participants attended an educational presentation and 130 participants completed both pre- and postsurveys (response rate 78%). Prepresentation, for all gestations, ≤ 50% of respondents correctly identified survival/intact survival rates. Postpresentation, correct responses regarding survival/intact survival rates ranged from 49 to 86% (p < 0.001) and attitudes shifted toward being more likely to resuscitate at all gestations regardless of parental wishes. There was a weak-to-modest relationship (Spearman's coefficient 0.24–0.40, p < 0.001–0.004) between knowledge responses and attitudes.Conclusion Attendance at an educational presentation did improve HCP knowledge about survival and long term outcomes for EPI, but HCP still underestimated survival and were not always willing to resuscitate in accordance with parental wishes. These findings may represent barriers to some experts' recommendation to use shared decision-making with parents when considering the resuscitation options for their EPI.
Keywords: knowledge; attitudes; educational; survival; resuscitation; extremely preterm infant